Correction: Experimental and theoretical charge density distribution in Pigment Yellow 10. Issue 9 (6th February 2015) - Du, Jonathan J.; Váradi, Linda; Tan, Jinlong; Zhao, Yiliang; Groundwater, Paul W.; Platts, James A.; Hibbs, David E.
Abstract : Correction for 'Experimental and theoretical charge density distribution in Pigment Yellow 101' by Jonathan J. Du et al., Phys. Chem. Chem. Phys., 2015, DOI: ; Web:10.1039/c4cp04302b .